Product Innovation Traditional Pottery Crafts Gorontalo - Sudana, I Wayan; Hasmah, Hasmah (Corak, 2022)
Gorontalo’s traditional pottery crafts had stagnation and were nearly extinct because it is deserted by its users. Presumed it happened because the final products are less innovative. Thus they are unable to fulfill the dynamics of market demand. This study aims to innovate Gorontalo’s traditional pottery products to be able to regain interest in the market. Studies use the method of art creation that is done through several stages: 1) exploration to discover the concept of design creation; 2) Designing to visualize the concept into visual design; 3) realizing of the design into the product prototype; 4) evaluation in order to envision market prospects. Throughout the process of research, six innovative pottery prototypes were made. The innovative value of these prototypes appears to the uniqueness of forms and finishing’s color variation. The distinctiveness of each prototype is reflected on the cultural art image of Gorontalo and forms of endemic animal of Sulawesi, which became the origin of the creation idea. Based on the evaluation, these all prototypes are said to have promising market prospects and worthy of production. Therefore, traditional Gorontalo pottery craftmens are advised to produce such prototypes to fulfill the dynamic demand of the market so that traditional pottery products do not lose consumers.